The earliest European Acheulean: new insights into the large shaped tools from the late Early Pleistocene site of Barranc de la Boella (Tarragona, Spain) - Ollé, Andreu; Lombao, Diego; Asryan, Lena; García-Medrano, Paula; Arroyo, Adrián; Fernández-Marchena, Juan Luis; Yeşilova, Görkem C.; Cáceres, Isabel; Huguet, Rosa; López-Polín, Lucía; Pineda, Antonio; García-Tabernero, Antonio; et al. (Frontiers in Earth Science, 2023)
Since the oldest known Acheulean lithic techno-typological features in Europe were reported at the site of Barranc de la Boella (Tarragona, Spain) continuous fieldwork has been conducted there in archeological deposits of late Early Pleistocene age (0.99-0.78 Ma). As a result, the excavation in two of the three open-air localities has significantly increased and expanded the collection of lithic and faunal remains, allowing us to make progress in the interpretation of the hominin behaviors in an open-air fluvial-deltaic sedimentary environment. The aim of this paper is to present an updated and comprehensive study of the collection of large shaped tools recovered so far to assess their significance in the framework of the earliest occurrence of the Acheulean in Europe. Large shaped tools of Barranc de la Boella’s Unit II include choppers as well as standard Acheulean forms such as picks, knives, and cleaver-like forms. Technological analyses revealed a combination of elements, consisting of a basic heavy-duty component obtained through simple shaping sequences coupled with significantly more elaborate tools produced on various large blanks (cobbles, slabs, or flakes), the trihedral pick being an outstanding example. The complete bifacial and bilateral shaping have yet to be documented, but the present specific tool assemblage attests to the Early Acheulean technological threshold. The archaeological record from Barranc de la Boella, therefore, contributes crucial data to the debate on the variability of the Lower Paleolithic cultural traditions involved in the human settlement of Western Europe during the Early Pleistocene, and, more specifically, on the first appearance of the Acheulean technology in this region. The results of this study revealed a technological assemblage unique in the known late Early Pleistocene archeological record from Europe, different from the rest of ancient Acheulean sites in this continent, which are dated at the Middle Pleistocene. This lends support to the hypothesis that Barranc de la Boella may represent a previously unrecognized Early Acheulean dispersion out of Africa connected to its first evidence at the gates of Eurasia, potentially moving over the northern Mediterranean coastal road to reach Western Europe.